Evaluación Académica del Ingeniero Agrónomo, Planes de Estudios y Tutoría Universitaria. Caso Universidad de Guanajuato - Córdova Duarte, Gabriel; Barbosa Jaramillo, Elva Rosa; Victorino Ramírez, Liberio; Montesinos Silva, Genaro (Acta Universitaria, 2006)
The present study was developed in order to establish the areas, of the curricula of the Agronomist program presently in effect at the University of Guanajuato, that require specific academic attention in order to prepare the graduates for the and increase their performance in the General Test for Undergraduates. (EGEL for the Spanish acronym). A comparison was carried out between the EGEL areas and those of the quarterly curriculum currently in effect in the Agricultural Science Institute of the University of Guanajuato, as well as the areas in those plans, the average scores of the subjects obtained in the EGEL were correlated with the score obtained in that test. The statistical methods used were students´ and correlation coefficient. The statistical differences and correlations indicate and improvement in the academic preparation in the areas of Environmental Protection Impact and the Handling of Resources, and also the need to raise the educational level and increase the tutoring in the courses of the areas such as Related Disciplines, Soils and Water, Health, and Rural Development. Nevertheless, attention must be paid to the majority of the courses, since the undergraduate on the semester plan obtained lower scores in the EGEL than those of quarterly plan.